Effect of aging temperature on microstructure and mechanical properties of different rolling orientations in novel Al–Li alloy. (August 2014) - Du, Z. L.; Zeng, W. D.; Yang, W. H.; Zhang, C.; Shi, C. L.; Wang, H. J.; Zhou, Z. P.
Abstract : Microstructure and properties of different rolling orientation with aging temperature varying in a newly developed Al–Li alloy was investigated by transmission electron microscopy (TEM) analysis. Sheets of experimental Al–Li alloy were solution treated at 510°C for 2 h. Predeformation of ∼3% was stretched in the 0 and 90° angle with respect to the original rolling orientation before aging treatment. All specimens were aged for 35 h at 138, 143, 148, 153, 158 and 163°C respectively. Tensile specimens were stretched along the previous orientation of predeformation. The results showed that the main strengthening phases in the alloy were δ ′ (Al3 Li), θ ′ (Al2 Cu)/ θ ″ (Guinier–Preston II zone), δ ′/ β ′ (Al3 Zr) and T1 (Al2 CuLi) phase. Among the phases above, the strengthening effect of T1 phase surpassed the others. Moreover, very little of cubic σ (Al5 Cu6 Mg2 ) phase was observed in the alloy. The microstructure evolution was similar via comparing sheets in different stretched directions. At initial stage of aging, a large amount of fine T1, δ ′, δ ′/ β ′ and θ ′/ θ ″ phases uniformly distributed in Al matrix with the aging temperature increasing. Subsequently, the quantity and size of T1 phase increased gradually. In the middle and later period, T1 phase was the main phase that grew at the cost of other phases. The peak aged temperature was 158°C with yield strength of 540 MPa when stretched at 0° angle to the original rolling orientation and 501 MPa when at 90° angle to the rolling direction. Meanwhile, the elongations were 9·5 and 10·9% respectively, which indicated that the anisotropy of the alloy was not obvious.